Targeting Mortalin by Embelin Causes Activation of Tumor Suppressor p53 and Deactivation of Metastatic Signaling in Human Breast Cancer Cells. - Nupur Nigam (PLoS ONE, 2015)
Embelin, a natural quinone found in the fruits of Embelia ribes, is commonly used in Ayurvedic home medicine for a variety of therapeutic potentials including anti-inflammation, anti-fever, anti-bacteria and anti-cancer. Molecular mechanisms of these activities and cellular targets have not been clarified to-date. We demonstrate that the embelin inhibits mortalin-p53 interactions, and activates p53 protein in tumor cells. We provide bioinformatics, molecular docking and experimental evidence to the binding affinity of embelin with mortalin and p53. Binding of embelin with mortalin/p53 abrogates their complex resulted in nuclear translocation and transcriptional activation function of p53 causing growth arrest in cancer cells. Furthermore, analyses of growth factors and metastatic signaling using antibody membrane array revealed their downregulation in embelin-treated cells. We also found that the embelin causes transcriptional attenuation of mortalin and several other proteins involved in metastatic signaling in cancer cells. Based on these molecular dynamics and experimental data, it is concluded that the anticancer activity of embelin involves targeting of mortalin, activation of p53 and inactivation of metastatic signaling.